What Is Widening Participation and Why Does It Matter? - Cupitt, C.; Trinidad, Sue (2016)
© 2017 M. Shah and G. Whiteford. Published by Elsevier Ltd. All rights reserved.The drivers of social justice, social inclusion, and an investment in human capital within the competitive global economy have led to the massification of higher education in an international context. As universities widen participation of students from more diverse backgrounds, particularly low socioeconomic students, indigenous students, and regional and remote students, they need to consider better tracking of attrition and retention, and providing additional methods of support. The sector is continuing to improve evaluation of widening participation strategies and programs, and increasing opportunities and alternative pathways, building aspirations and community collaborations, and expanding institutional reforms. The context of these reforms, and their criticisms and strengths are considered in light of continuing efforts to solve these complex systemic inequities.